Exploring the potential of flubendazole in filariasis control: evaluation of the systemic exposure for different pharmaceutical preparations - Ceballos, Laura (2014)
The goal of elimination of the human filariases would benefit greatly from the use of a macrofilaricidal agent. In vivo trials in humans and many experimental animal models suggest that flubendazole (FLBZ) is a highly efficacious macrofilaricide. However, since serious injection site reactions were reported in humans after parenteral FLBZ administration, the search for alternative pharmaceutical strategies to improve the systemic availability of FLBZ and its metabolites has acquired urgency in both human and veterinary medicine. The goal of the current work was to compare the systemic exposure of FLBZ formulated as either an aqueous hydroxypropyl-b-cyclodextrin (CD) or aqueous carboxymethyl cellulose (CMC) suspension or a Tween 80-based formulation (TWEEN) in rats and jirds (Meriones unguiculatus). Healthy animals of both species were allocated into four experimental groups of 44 animals each: FLBZ-CDoral and FLBZ-CDsc, treated with the FLBZ-CD formulation by the oral or subcutaneous routes, respectively; FLBZ-TWEENsc, dosed subcutaneously with the FLBZ-TWEEN formulation; and FLBZ-CMCoral, treated orally with the FLBZ suspension. The FLBZ dose was 5 mg/kg. FLBZ and its hydrolyzed (H-FLBZ) and reduced (R-FLBZ) metabolites were recovered in plasma samples collected from rats and jirds treated with the different FLBZ formulations. In both species, FLBZ parent drug was the main analyte recovered in the bloodstream. In rats, FLBZ systemic exposure (AUC0-LOQ) was significantly (P,0.05) higher after the FLBZ-CD treatments, both oral (4.860.9 mg.h/mL) and subcutaneous (7.360.6 mg.h/mL), compared to that observed after oral administration of FLBZ-CMC suspension (0.9360.2 mg.h/mL). The same differences were observed in jirds. In both species, parenteral administration of FLBZ-TWEEN did not improve the systemic availability of FLBZ compared to FLBZ-CDoral treatment. In conclusion, formulation approaches that enhance the availability of flubendazole in the rat and jird may have therapeutic implications for a drug with poor or erratic bioavailability.